The empirical study on the determinants of gold price in Malaysia / Siti Noranisah Mohd Sunanin - Mohd Sunanin, Siti Noranisah (Faculty of Business Management, 2014)
This research determines the effects of macroeconomic variables to the price of gold in Malaysia. The variables to be considered are crude palm oil (CPO), exchange rate, inflation rate, silver price and rubber price in Malaysia. The secondary data are chosen in the research from 2002 until 2013. The research is using Multiple Linear Regression Model is used to determine the significant relationship between the dependent and independent variables. The result shows positive significant relationship by inflation rate (CPI) and silver price on the gold price. Whereas, the interest rate (BLR) and crude oil price shows negative significant relationship the price of gold.